POLITIK HUKUM AGRARIA DALAM PENYELESAIAN GANTI RUGI PENGADAAN TANAH UNTUK KEPENTINGAN UMUM - Kristianingsih Kristianingsih; Litari Elisa Putri; Nurfauziah Astiqmalia (Universitas Muhammadiyah Jember, 2020)
Land has social, economic and political characteristics for individual interests and public interests that are utilized by all Indonesia people. In the era of development that is increasingly developing at this time land is needed in the interests of development so as to create prosperity for the wider community. Land acquisition efforts undertaken by the state to be utilized and used in the public interest in principle contain respect for the legal right to land to obtain compensation. The purpose of the birth of the Land Acquisition Law is one of the principles of justice for holders of rights entitled to land. Normative constraints that arise in the practice of providing compensation for those entitled to land acquisition. In the political structure of agrarian law, the legal certainty of land rights is determined by the registration of land, but there are still conflicts over land ownership disputes against entitled land, especially minority communities that ultimately in land acquisition do not receive compensation. This study takes two studies, namely one, how is the settlement of compensation in land acquisition for public use? 2. What is the agrarian legal policy for those entitled to compensation for land acquisition? Politics of Agrarian law in the settlement of land acquisition compensation which states that land rights controlled by the State are fully used for the prosperity and welfare of the community and so that land used for public purposes must be surrendered by the government for development in the public interest with respect for proper compensation compensation against the rightful owner, which in this case is not only given to the owner of the land certificate but also the owner who is physically in possession of good faith and has been handed down as the land registration system in Indonesia.